Problem-solving challenges: operating a campus food pantry to improve student success. Issue 1 (2nd January 2020) - Price, Carmel E.; Watters, Emma; Reppond, Harmony A.; Sampson, Natalie R.; Thomas-Brown, Karen
ABSTRACT: As of June 2018, over 640 college campuses were registered with the College and University Food Bank Alliance, an organization that supports campuses currently operating or interested in opening a pantry. However, a dearth of research exists that examine how campus pantries function: what unique challenges do campus pantries face and how do pantry staff creatively address these challenges? In October 2016, researchers collected qualitative data during a problem-solving workshop at a daylong summit of 28 pantry representatives from 16 Michigan college campuses. Pantry staff documented their biggest challenges and then collectively brainstormed solutions. Researchers used consensus qualitative research coding procedures to generate common themes. Four overarching themes, and 11 sub-themes, emerged out of the 51 challenges and 117 solutions generated by participants: (1) infrastructure and resources, (2) operating within university systems, (3) building and sustaining partnerships, and (4) data, research, and assessment. The challenges and solutions generated by participants reflect the distinctiveness of campus pantry work relative to community-based pantries and underscore challenges and potential best practices of operating a pantry within a university system. These findings help campus administrators and pantry staff anticipate and address food security as an increasingly necessary strategy for student success and educational equity.